CALCULATION OF REINFORCED CONCRETE STRUCTURES TAKING INTO ACCOUNT INELASTIC PROPERTIES OF MATERIALS - Abobakirova Zebuniso Asrorovna (Journals Park Publishing, 2023)
The article provides a general description of methods for calculating statically indeterminate reinforced concrete structures and the influence of complex structural solutions, especially of monolithic reinforced concrete, which are widely used in modern construction. The conditions for the use of limit equilibrium methods for calculating the load-bearing capacity of structures, taking into account the increase in plastic deformations, are analyzed, and the rules that must be observed when designing reinforced concrete structures by the limit equilibrium method are proposed.
Keywords: statically indeterminate construction, inelastic properties, inelastic deformations, ultimate equilibrium, redistribution of forces.